Design and Simulation of the Thermionic Emission-Based Reltron Oscillator - Tripathi P.; Kumar A.; Dwivedi S.; Jain P.K. (My University, 2025)
In this article, we describe the design and simulation of a highly efficient thermionic emission-based reltron oscillator. First, the design process of the thermionic emission-based reltron has been presented, and then the RF interaction cavity has been modeled using a commercial tool 'CST Studio Suite.' In the absence of an electron beam, the electromagnetic behavior of the modeled RF interaction cavity has been investigated with the help of the eigenmode solver and frequency-domain solver. In addition, the structural parametric dependence on the resonant mode frequency of the RF interaction cavity has been also investigated. The RF behavior of the designed reltron device has been simulated using particle-in-cell (PIC) solver. An electrical parametric analysis has been performed to evaluate the performance of the modeled device. Finally, the simulation results predicted that the device is capable of producing 22 MW of RF power with a pulsewidth of 5 μs and an efficiency of 44%. For validation, the simulated results have been compared with the previously reported experimental results, we found that the result variation is less than 5%, which shows a good agreement with the reported experimental results. © 2020 IEEE.